Process for the preparation of an adsorbent for oxygen-containing organic compounds
By introducing a coupling agent, copper ions, and titanium ions into 13X molecular sieve, a highly efficient and stable adsorbent for oxygen-containing organic compounds was prepared, solving the problem of low adsorption efficiency in existing technologies and achieving efficient removal of oxides. This adsorbent is suitable for the purification of Fischer-Tropsch synthesis products and hydrocarbon fuels.
Patent Information
- Application Number
- CN202410976184.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2025-12-12
- Estimated Expiration
- 2044-07-19
AI Technical Summary
Existing oxygen-containing organic compound adsorbents have low adsorption efficiency, making it difficult to effectively remove oxides from Fischer-Tropsch synthesis products and affecting the purity of olefin and alkane products.
A modified oxygen-containing organic compound adsorbent is formed by introducing a coupling agent, copper ions, and titanium ions into 13X molecular sieve and impregnating and calcining it during the preparation process.
It improves the chemical and thermal stability of the adsorbent, significantly enhances the adsorption efficiency for oxides, and is suitable for the removal of oxides from high-carbon alkanes and alkenes produced by Fischer-Tropsch synthesis, as well as from a wide range of hydrocarbon fuels or chemical products.
Smart Images

Figure BDA0004954578310000151 
Figure BDA0004954578310000152 
Figure BDA0004954578310000161
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of chemical synthesis, in particular, to a preparation method of an oxygen-containing organic compound adsorbent. BACKGROUND
[0002] Fischer-Tropsch synthesis is a technology for producing hydrocarbon products from coal through direct or indirect liquefaction, which is a core process step in coal chemical industry. In addition to a wide range of carbon number distribution of hydrocarbons, Fischer-Tropsch synthesis oil also contains a wide range of carbon number distribution of alcohols, aldehydes, ketones, acids, esters and other oxygen-containing compounds (referred to as oxygen-containing organic compounds in the present application). The presence of oxygen-containing compounds will affect the purity of subsequent olefin and alkane products, and further affect the production of downstream products, so the separation and removal of oxygen-containing compounds need to be carried out before the separation of α-olefin and alkane. At present, the methods for removing oxygen-containing compounds in oil products mainly include hydrogenation refining, solvent liquid-liquid extraction, azeotropic distillation and reaction conversion. Liquid-liquid extraction is the most widely used technology, but liquid-liquid extraction will face the problem of insufficient extraction depth and the need for multiple extractions, which not only increases the frequency of operation, but also brings higher equipment investment costs. Adsorption removal of oxygen-containing compounds is a very promising removal technology, and most of the adsorbents selected in related technologies are molecular sieve adsorbents. Molecular sieve is a silicate, which has uniform pore size, regular crystal structure, rich pore system, large specific surface area, good thermal stability and other characteristics, and is considered to be the preferred adsorbent material for removing oxygen-containing compounds in olefins. Among them, the pore size of FAU type (X, Y type) molecular sieve is about 0.74 nm. In particular, X-type molecular sieve can better remove oxygen-containing impurities in olefins, and is more studied and applied in industrial practice.
[0003] At present, since the hydrocarbon products produced by Fischer-Tropsch synthesis of coal have different carbon number distribution, the oxygen-containing compounds in each carbon number product are also various, their molecular weight and molecular structure are quite different, and the pore size and composition of commonly used molecular sieves are also different, so there is no adsorbent suitable for all carbon number distribution Fischer product for separating oxygen-containing compounds. Therefore, the oxygen-containing compound adsorbent with uniform and ordered micropores, large specific surface area, large adsorption capacity, and low adsorption heat has broad application prospects in the field of adsorption separation.
[0004] Existing technologies for synthesizing 13X molecular sieves suffer from low silicon source utilization, difficulty in controlling product size and morphology, and poor dispersibility. CN103523796B proposes a method for preparing submicron X-type molecular sieves, focusing on hydrocarbon separation and adsorption. First, silica sol is used as the silicon source to prepare a directing agent. A molecular sieve mother liquor is prepared from water glass, sodium hydroxide, aluminum hydroxide, or sodium aluminate. The directing agent is then added to this mother liquor, followed by aging, the addition of a weakly polar dispersant, and microwave-assisted crystallization to obtain the submicron X-type molecular sieve. The resulting X-type molecular sieve has small crystal grains, shortens the synthesis time, and reduces production costs. The resulting adsorbent product has a large adsorption capacity and is easily regenerated, making it suitable for deep removal of oxygen-containing impurities from hydrocarbon streams. However, the adsorption efficiency of the oxygen-containing organic compound adsorbent still needs further improvement. Summary of the Invention
[0005] The main objective of this invention is to provide a method for preparing an oxygen-containing organic compound adsorbent, so as to solve the problem of low efficiency of oxygen-containing organic compound adsorbents in the prior art.
[0006] To achieve the above objectives, according to one aspect of the present invention, a method for preparing an oxygen-containing organic compound adsorbent is provided, the method comprising: introducing a coupling agent, copper ions and titanium ions into a 13X molecular sieve to obtain the above-mentioned oxygen-containing organic compound adsorbent;
[0007] The preparation method of the aforementioned 13X molecular sieve includes:
[0008] Step S1: After mixing the aluminum source and silicon source with water respectively, aluminum-containing materials and silicon-containing materials are obtained;
[0009] Step S2: Mix the aluminum-containing material and the silicon-containing material, and then stir, adjust the pH value and crystallize in sequence to obtain a crystallized product.
[0010] Step S3: The material containing molecular sieves is subjected to aluminum and silicon dissolution treatment, and the resulting aluminum-rich liquid and silicon-rich liquid are mixed to obtain a gel-like mother liquor.
[0011] Step S4: After mixing the above crystallized product and the above gel-like mother liquor, the mixture is subjected to aging, hydrothermal crystallization, filtration, washing and drying in sequence to obtain the above 13X molecular sieve.
[0012] The above-mentioned molecular sieve-containing materials are selected from any one or more of the following: waste ZSM-5 molecular sieve catalyst, waste MTO catalyst, waste molecular sieve adsorbent, fly ash, waste FCC catalyst or waste VOCs adsorbent.
[0013] Further, the 13X molecular sieve and the coupling agent are added into an alcohol solvent, and then solid-liquid separation and first calcination are sequentially performed to obtain an adsorbent precursor; the adsorbent precursor is soaked in a copper salt solution, and then mixed with a precursor sol formed by mixing a titanium source, ethanol and water, and sequentially subjected to first drying, second calcination and second drying to obtain the adsorbent for oxygen-containing organic compounds.
[0014] Further, the coupling agent includes isopropyl trimethoxysilane, vinyl trimethoxysilane, ethyl silicate, ethoxysilane or ethyl silicate.
[0015] Further, the alcohol solvent includes ethanol, propanol or butanol.
[0016] Further, the copper salt solution includes copper nitrate, copper chloride or copper acetate.
[0017] Further, the titanium source includes tetrabutyl titanate, titanium silicate or titanium diisopropoxy bisacetylacetone.
[0018] Further, the mass ratio of the 13X molecular sieve, the coupling agent and the alcohol solvent is 1:(0.01-0.05):(0.8-1.5).
[0019] Further, the first calcination is performed at a temperature of 400-500°C for 0.5-4h.
[0020] Further, the mass ratio of the adsorbent precursor and copper ions in the copper salt solution is 1:(0.01-0.05); preferably, the adsorbent precursor is soaked in the copper salt solution for 18-30h; preferably, the adsorbent precursor is mixed with the precursor sol for 6-8h at a temperature of 60-80°C.
[0021] Further, the precursor sol is prepared by stirring the titanium source, the ethanol and the water, and the stirring is performed at a temperature of 50-70°C for 1-6h.
[0022] Further, the mass ratio of the titanium source, the ethanol and the water in the precursor sol is 1:(3-7):(0.5-1.5).
[0023] Further, the first drying is performed at a temperature of 90-110°C for 6-18h.
[0024] Further, the second calcination is performed at a temperature of 450-550°C for 0.5-4h.
[0025] Further, the second drying is performed at a temperature of 70-90°C for 8-16h.
[0026] Further, the aluminum source is selected from any one or more of sodium aluminate, pseudo-boehmite, aluminum sulfate or aluminum nitrate.
[0027] Further, the silicon source is selected from any one or more of silica sol, tetraethyl orthosilicate, macro-porous silica gel, silicon powder, fly ash or white carbon black.
[0028] Further, the stirring conditions in step S2 are 20-100°C for 0.1-24h.
[0029] Further, the crystallization is two-stage crystallization, wherein the first-stage crystallization is at 20-60°C for 4-24h, and the second-stage crystallization is at 80-120°C for 6-48h; the crystallization is performed in a hydrothermal reactor; and the second-stage is 20°C higher than the first-stage.
[0030] Further, the molar ratio of the components in the crystallization product is SiO2 / Al2O3 = 0.01-2.5:1, Na2O / SiO2 = 0.01-4.0:1, and H2O / SiO2 = 1.0-40.0:1.
[0031] Further, the steps of dissolving aluminum and dissolving silicon are as follows:
[0032] 1) The ground material containing molecular sieve with particle size less than 200 mesh is mixed with Na2CO3 at a mass ratio of 1:0.5-1:5, and a calcination product is obtained by calcining at 550-800°C for 60-120min. The calcination product is dissolved in a monobasic acid with a mass fraction of 10%-35%, and a filtrate and a residue are obtained by filtration. The filtrate is the aluminum-rich solution.
[0033] 2) The residue is mixed with NaOH and H2O at a mass ratio of (2-100):(40-60):(50-400), stirred, and filtered to obtain the silicon-rich solution.
[0034] Further, the molar ratio of the components in the gel-like mother liquor is SiO2 / Al2O3 = (0.5-6.0):1, Na2O / SiO2 = (0.5-6.0):1, and H2O / SiO2 = (10-100):1.
[0035] Further, the amount of the crystallization product added is 5wt%-20wt% of the gel-like mother liquor.
[0036] Further, the aging temperature is 20-100°C, and the aging time is 0.1-24h. The aging process is performed under stirring.
[0037] Further, the temperature of the hydrothermal crystallization is 60-150℃, and the time is 0.1-36h.
[0038] By introducing the coupling agent for coupling metal ions and the impregnation treatment of copper ions and titanium ions on the basis of the 13X molecular sieve, the surface and structure of the molecular sieve are modified, and thus the improved oxygen-containing organic compound adsorbent is obtained. The adsorbent has excellent chemical stability, thermal stability and high adsorption efficiency for oxides, overcomes the low adsorption efficiency of the oxygen-containing organic compound adsorbent in the prior art, and is not only excellent in removing oxides from the Fischer-Tropsch synthesis high-carbon alkane-alkene product, but also suitable for efficient removal of oxides in a wide range of hydrocarbon fuels or chemical products, thereby providing a high-efficiency, stable and controllable solution for the related field. DETAILED DESCRIPTION
[0039] It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict. The present application will be described in detail below with reference to the embodiments.
[0040] As mentioned in the background, the adsorption efficiency of the oxygen-containing organic compound adsorbent in the prior art is low and needs to be further improved. Therefore, developing an oxygen-containing organic compound adsorbent with high adsorption efficiency helps to solve the problem that the oxygen-containing compounds in the Fischer-Tropsch synthesis oil product process have too great an impact on the purity of the subsequent olefins and alkanes. Molecular sieve is a silico-aluminate with uniform pore size, regular crystal structure, rich pore system, large specific surface area and good thermal stability, and is considered as a preferred adsorbent material for removing oxygen-containing compounds from olefins.
[0041] Therefore, in the present application, the inventors attempt to use molecular sieve as a raw material and introduce a coupling agent, copper ions and a titanium source into the molecular sieve to significantly improve the adsorption capacity of the oxygen-containing organic compound adsorbent for oxygen-containing compounds and further enhance the adsorption performance of the oxygen-containing organic compound adsorbent, on the basis of which the protection scheme of the present application is proposed.
[0042] In a first typical embodiment of the present application, a preparation method of an oxygen-containing organic compound adsorbent is provided, which comprises introducing a coupling agent, copper ions and a titanium source into a 13X molecular sieve to obtain the oxygen-containing organic compound adsorbent.
[0043] The preparation method of the 13X molecular sieve comprises:
[0044] In step S1, the aluminum source and the silicon source are mixed with water respectively to obtain aluminum-containing material and silicon-containing material;
[0045] In step S2, the aluminum-containing material and the silicon-containing material are mixed, and stirring, pH adjustment and crystallization treatment are sequentially performed to obtain a crystallization product.
[0046] Step S3, the molecular sieve-containing material is subjected to aluminum and silicon dissolution treatment, and the obtained aluminum-rich liquid and silicon-rich liquid are mixed to obtain a gel-like mother liquor;
[0047] Step S4, after the above crystallization product and the above gel-like mother liquor are mixed, aging, hydrothermal crystallization, filtration, washing and drying are sequentially performed to obtain the above 13X molecular sieve;
[0048] The molecular sieve-containing material is selected from any one or more of the following: waste ZSM-5 molecular sieve catalyst, waste MTO catalyst, waste molecular sieve adsorbent, fly ash, waste FCC catalyst or waste VOCs adsorbent.
[0049] The 13X molecular sieve can provide more adsorption sites and mesoporous channels (2-50 nm), increase the pore volume inside the molecular sieve crystal, and can improve the flow and diffusion performance of guest molecules inside the molecular sieve, and the morphology is uniformly dispersed, which is a regular nanoparticle. In addition, the 13X molecular sieve of the present application has a high silicon-aluminum ratio, high silicon source utilization rate, good selectivity, and can be adjusted according to different adsorbed molecules, thereby significantly reducing the carbon deposition rate of the molecular sieve, improving the diffusion performance of the adsorbent, and is a good material for preparing oxygen-containing organic compound adsorbents.
[0050] The introduction of the coupling agent helps to combine the coupling agent with the surface of the 13X molecular sieve, thereby further facilitating the introduction of copper ions and titanium sources. The introduction of the copper ions can strengthen the acidity of the molecular sieve and improve the catalytic activity. The introduction of the titanium source can enhance the structural stability of the molecular sieve and improve the thermal stability.
[0051] The specific introduction method of the coupling agent, copper ions and titanium source is not limited, including but not limited to impregnation method, ion exchange method and chemical vapor deposition method. Specifically, the existing introduction method can be optimized or improved. In a preferred embodiment of the present application, the 13X molecular sieve and the coupling agent are added to an alcohol solvent, and solid-liquid separation and first calcination are sequentially performed to obtain an oxygen-containing organic compound adsorbent precursor; the adsorbent precursor is soaked in a copper salt solution, and then mixed with a precursor sol formed by mixing the titanium source, ethanol and water, and sequentially subjected to first drying, second calcination and second drying to obtain the above oxygen-containing organic compound adsorbent.
[0052] In the above embodiments, the adsorbent has the beneficial effects of significantly improving the adsorption capacity of 13X molecular sieve for oxygen-containing organic compounds and improving the selectivity by introducing the coupling agent, copper ions and titanium source in the above manner. The coupling agent can be selected from any one or more of isopropyl trimethyl silane, vinyl trimethyl silane, ethyl silicate, ethoxy silane or ethyl silicate. The copper ions can be selected from copper nitrate, copper chloride or copper acetate. Similarly, the source of titanium is also diverse, including tetrabutyl titanate, titanium silicate or titanium diisopropoxy diacetylacetone. The alcohol reagent includes ethanol, propanol or butanol.
[0053] The requirements for adsorption performance are different according to the application scenarios of VOCs adsorbent, and the specific parameters and conditions of each step are also different. In a preferred embodiment of the present application, the molar ratio of the 13X molecular sieve, the coupling agent and the alcohol solvent is 1:(0.01-0.05):(0.8-1.5) (with the beneficial effects of improving coupling efficiency and ensuring uniformity of the adsorbent preparation). After solid-liquid separation, the 13X molecular sieve needs to be calcined at 400-500°C for 0.5-4h to ensure complete removal of the organic template (coupling agent) to obtain the adsorbent precursor.
[0054] The molar ratio of the adsorbent precursor to the copper ions in the copper salt solution is different, and accordingly the time for the adsorbent precursor to soak in the copper salt solution can be adjusted accordingly. In a preferred embodiment of the present application, when the mass ratio of the adsorbent precursor to the copper ions in the copper salt solution is 1:(0.01-0.05); preferably, the adsorbent precursor is soaked in the copper salt solution for 18-30h. The purpose of this step is to ensure uniform distribution of copper ions on the molecular sieve and avoid excessive deposition affecting the adsorption performance.
[0055] The precursor solution is a mixture of titanium source, ethanol and water, which has the effect of increasing the dispersity and uniformity of the titanium source on the molecular sieve. The ratio of the titanium source, ethanol and water in the precursor solution can be adjusted according to actual needs. In a preferred embodiment of the present application, the mass ratio of the titanium source, ethanol and water is 1:(3-7):(0.5-1.5), which helps to adjust the viscosity and stability of the precursor sol. After the adsorbent precursor is soaked in the copper salt and the precursor sol, it needs to be sequentially subjected to first drying, second calcination and second drying. The first drying conditions are 90-110°C for 6-18h. The adsorbent is calcined at 450-550°C for 0.5-4h, which helps to further fix the copper ions and titanium source and remove the residual coupling agent. Finally, the adsorbent is dried at 70-90°C for 8-16h to obtain the adsorbent precursor.
[0056] The preparation method of the 13X molecular sieve comprises:
[0057] Step S1: The aluminum source and the silicon source are mixed with water respectively to obtain an aluminum-containing material and a silicon-containing material. The silicon source is selected from one or more of silica sol, tetraethyl orthosilicate, coarse-pored silica gel, silicon powder, fly ash, and white carbon black. The silicon source and water are mixed at 20-60°C for 0.1-12h with stirring at a stirring speed of 200-800rpm to obtain the silicon-containing material, which has a concentration of 28-99wt%. The aluminum source is selected from one or more of sodium aluminate, pseudo-boehmite, aluminum sulfate, and aluminum nitrate.
[0058] The aluminum source and water are mixed at 20-60°C for 0.1-12h with stirring at a stirring speed of 200-800rpm to obtain the aluminum-containing material, which has a concentration of 15-99wt%. A suitable stirring temperature, time, and speed can ensure better dissolution of the aluminum source and the silicon source, and the silicon-containing material and the aluminum-containing material having the above-mentioned concentrations have good compatibility, which helps subsequent mixing to be more uniform and the reaction to be more complete.
[0059] Step S2: The aluminum-containing material and the silicon-containing material are mixed, and then stirring, pH adjustment, and crystallization treatment are sequentially performed to obtain a crystallization product. The aluminum-containing material and the silicon-containing material are stirred at 20-100°C for 0.1-24h to obtain a mixture gel of the aluminum source and the silicon source, which is prepared for subsequent preparation of the molecular sieve. The mixture gel needs to be adjusted in pH value, and the adjusted pH value is 8.5-12.5, which is alkaline. The alkaline environment helps better mixing and reaction of the silicon source and the aluminum source, thereby improving the silica-alumina ratio, the specific surface area, and the pore volume of the molecular sieve.
[0060] The method for adjusting the pH value is not specifically limited, and a solid base or an aqueous solution of a base can be slowly added to the mixture gel. In addition, the mixture gel needs to be subjected to crystallization treatment, and the crystallization is divided into two stages. In the first stage, the crystallization temperature is 20-60°C, and the crystallization time is 4-24h. The first crystallization makes the crystal type of the molecular sieve more complete and uniform. In the second stage, the crystallization temperature is 80-120°C, and the crystallization time is 6-48h. The second crystallization can further improve the completeness and uniformity of the crystal type of the molecular sieve.
[0061] In a preferred embodiment of the present application, the crystallization is carried out in a hydrothermal reactor, and the second-stage crystallization temperature is 40°C higher than the first-stage crystallization temperature. The inventors have found through a large number of experiments that when the second-stage crystallization temperature is 40°C higher than the first-stage crystallization temperature, the molar ratio of the components in the crystallization product can be further optimized, thereby effectively improving the adsorption property. The molar ratio of the components in the crystallization product is SiO2 / Al2O3=(0.01-2.5):1, Na2O / SiO2=(0.01-4.0):1, and H2O / SiO2=(1.0-40.0):1. Defining the molar ratio of the components helps to obtain a better pore structure, thereby obtaining a VOC adsorbent with excellent adsorption property in the subsequent preparation process.
[0062] Preferably, the pH is 11.8-12.2, the first-stage crystallization temperature is preferably 35-45°C, the time is 11-13h, the second-stage crystallization temperature is preferably 90-100°C, the time is 22-26h, the second-stage temperature is 50-60°C higher than the first-stage temperature, and the molar ratio of the components in the crystallization product is SiO2 / Al2O3=(4.6-5.0):1, Na2O / SiO2=(1.8-2.0):1, and H2O / SiO2=40-50:1. The inventors have found through long-term experiments that by precisely controlling the pH, the crystallization temperature, and the raw material ratio, the pH is 12, the first-stage crystallization temperature is 40°C, the time is 12h, the second-stage crystallization temperature is 95°C, the time is 24h, the molar ratio of the components in the crystallization product is SiO2 / Al2O3=4.7:1, Na2O / SiO2=1.95:1, and H2O / SiO2=44:1, which collectively controls the uniform arrangement of pores, the specific surface area, and the pore volume, thereby preparing a molecular sieve with excellent performance.
[0063] Step S3: The molecular sieve-containing material is subjected to aluminum dissolution and silicon dissolution treatment to obtain an aluminum-rich liquid and a silicon-rich liquid, and the obtained aluminum-rich liquid and silicon-rich liquid are mixed to obtain a gel-like mother liquor. It should be noted that the molecular sieve-containing material is selected from any one or more of the following: waste ZSM-5 molecular sieve catalyst, waste MTO catalyst, waste molecular sieve adsorbent, fly ash, waste FCC catalyst, or waste VOCs adsorbent. The use of waste catalysts to prepare 13X molecular sieves solves the problem of waste catalyst resource waste, and also reduces the production cost of 13X molecular sieves. The entire production process is economical and environmentally friendly.
[0064] The process of dissolving aluminum and silicon in the above-mentioned molecular sieve-containing material can be appropriately changed according to actual needs. In a preferred embodiment of the present application, the above-mentioned steps of dissolving aluminum and silicon are as follows: 1) the above-mentioned molecular sieve-containing material after grinding to less than 200 mesh is mixed with Na2CO3 in a mass ratio of 1:(0.5-1):5, and then calcined at 550-800°C for 60-120 min to obtain a calcined product. The calcined product is dissolved in a monobasic acid with a mass fraction of 10%-35%, and then filtered to obtain a filtrate and a residue. The filtrate is the above-mentioned aluminum-rich liquid; 2) the residue is mixed with NaOH and H2O in a mass ratio of (2-100):(40-60):(50-400), stirred, mixed uniformly, and filtered to obtain the above-mentioned silicon-rich liquid. The process of dissolving aluminum and silicon is simple to operate, and the filtering residue for preparing the aluminum-rich liquid can be directly used as a raw material for producing the silicon-rich liquid, thereby further reducing the production cost of the molecular sieve.
[0065] Step S4: the above-mentioned crystallization product of step S2 and the above-mentioned gel-like mother liquor of step S3 are mixed, and then aging, hydrothermal crystallization, filtration, washing and drying are performed to obtain the above-mentioned 13X molecular sieve. The amount of the crystallization product added accounts for 5wt%-20wt% of the gel-like mother liquor. The amount of the crystallization product is limited to ensure that there is enough silicon-aluminum source in the gel-like mother liquor to participate in the crystallization reaction, and to avoid uneven reaction caused by too much crystallization product, which affects the distribution of active sites of the molecular sieve and the pore volume performance of the molecular sieve.
[0066] In order to further optimize the crystal form and enhance the stability of the 13X molecular sieve, the mixture of the crystallization product and the gel-like mother liquor needs to be subjected to aging treatment. The conditions for the above-mentioned aging are as follows: the aging temperature is 20-100°C, the aging time is 0.1-24 h, and the aging process is carried out under stirring, which can make the crystal structure more uniform and the crystal size more uniform. The hydrothermal crystallization temperature is 60-150°C, and the crystallization time is 0.1-36 h, which has the beneficial effects of promoting the growth of the molecular sieve crystals and perfecting the crystal form, and improving the thermal stability and stability of the crystals. Then, the reaction product is filtered and washed to neutral, and dried at 80-120°C until no obvious weight loss to obtain the 13X molecular sieve.
[0067] The beneficial effects of the present application will be further explained in detail in combination with specific examples.
[0068] Example 1
[0069] (1) Preparation of 13X molecular sieve seeds
[0070] Dissolve 21.0 g of silica sol (mass fraction 30%) in 36.0 g of deionized water, and after pretreatment at 25°C and 500 rpm for 1 h in a closed reaction kettle, obtain a dispersion phase aqueous solution of the silicon source; dissolve 24 g of aluminum sulfate in 18.0 g of deionized water, and after stirring at 25°C and 500 rpm for 1 h, obtain a dispersion phase aqueous solution of the aluminum source; slowly drop the aqueous solution of the aluminum source into the aqueous solution of the silicon source, and continue stirring at 60°C for 8 h to obtain a mixed system; dissolve 6.74 g of sodium hydroxide in 36 g to obtain a NaOH solution.
[0071] Add the NaOH solution to the mixed system, and control the pH value to be maintained at 12 to obtain a gel system. Place the gel system in a hydrothermal reaction kettle, and perform two-stage temperature control crystallization; the first-stage crystallization is performed at 40°C for 12 h, and the second-stage crystallization is performed at 95°C for 24 h; during the crystallization process, add deionized water as needed to obtain 13X molecular sieve seeds, wherein the molar ratio of the components is: SiO2 / Al2O3 = 1.5:1, Na2O / SiO2 = 1.6:1, and H2O / SiO2 = 32:1.
[0072] (2) Preparation of 13X molecular sieve (introduction of waste catalyst)
[0073] Mix 10 g of 200-mesh waste ZSM-5 molecular sieve catalyst (see Table 1 for the composition) with 8 g of 10% by mass Na2CO3, and uniformly calcine at 650°C for 120 min, and then dissolve and filter the calcination product with a 25% by mass nitric acid solution to obtain 1.2 mol / L of an aluminum-rich liquid for standby use. Mix 10 g of the filtered residue, 6 g of NaOH, and 40 g of H2O to obtain 2 mol / L of a silicon-rich liquid, and finally mix the silicon-rich liquid and the aluminum-rich liquid in a weight ratio of 4:1 to obtain a gel-like mother liquor, wherein the molar ratio of SiO2 to Al2O3 in the gel-like mother liquor is 3.5:1, the molar ratio of Na2O to SiO2 is 2.8:1, and the molar ratio of H2O to SiO2 is 80:1.
[0074] Add 25 g of 13X molecular sieve seeds to the gel-like mother liquor, and continue stirring at 60°C for 12 h of aging, and then place it in a hydrothermal reaction, and perform crystallization at 98°C for 24 h; filter and wash the reaction product until the pH is 7, and then dry at 90°C to obtain 13X molecular sieve.
[0075] (3) Preparation of an oxygen-containing organic compound adsorbent
[0076] Copper salt solution soaking treatment: 50 g of 13X molecular sieve and 0.5 g of methyl triethoxysilane (MTES) were added to 49.5 g of anhydrous ethanol, and the reaction was stirred at room temperature for 4 h. Then, the molecular sieve was filtered, and the filtered molecular sieve was calcined at 450 °C for 2 h. The calcined 13X molecular sieve was soaked in a 1 mol / L copper nitrate solution at room temperature, and the mass ratio of the 13X molecular sieve to copper ions was 1:0.03, and the soaking was continued for 18 h.
[0077] Titanium precursor sol treatment: 10 g of tetrabutyl titanate was slowly added dropwise to a mixed solvent of 50 g of ethanol and 10 g of distilled water, and the mixture was stirred at 60 °C for 3 h to obtain a precursor sol.
[0078] The soaked 13X molecular sieve was added to the precursor sol, and the mixture was stirred (for 8 h at 60 °C), and then the mixture was dried at 100 °C for 12 h, and then the mixture was heated to 500 °C at a heating rate of 5 °C / min in a kiln, and the mixture was kept at 500 °C for 2 h. The calcined product was dried in a vacuum drying device for 12 h, and finally an oxygen-containing compound adsorbent was obtained.
[0079] Example 2
[0080] (1) Preparation of 13X molecular sieve seeds
[0081] This step is the same as (1) in Example 1.
[0082] (2) Preparation of 13X molecular sieve (introduction of waste catalyst)
[0083] 12 g of 200-mesh waste 13X adsorbent (see Table 1 for composition) was mixed with 10 g of 10% by mass Na2CO3, and the mixture was calcined at 650 °C for 120 min, and then the calcined product was dissolved in a 15% by mass nitric acid solution to obtain a 1.5 mol / L aluminum-rich solution, and the residue obtained by filtration was mixed with 6 g of NaOH and 40 g of H2O to obtain a 0.8 mol / L silicon-rich solution, and finally the silicon-rich solution and the aluminum-rich solution were mixed in a weight ratio of 3.5:1 to obtain a gel-like mother liquor, and the molar ratio of SiO2 to Al2O3 in the gel-like mother liquor was 1.8:1, the molar ratio of Na2O to SiO2 was 4.5:1, and the molar ratio of H2O to SiO2 was 50:1.
[0084] 15 g of 13X molecular sieve seeds were added to the gel-like mother liquor, and the mixture was continuously stirred and aged at 60 °C for 12 h, and then the mixture was placed in a hydrothermal reactor, and the crystallization temperature was 95 °C, and the crystallization time was 24 h, and then the reaction product was filtered and washed until the pH was 7, and then the product was dried at 90 °C to obtain 13X molecular sieve.
[0085] (3) Preparation of oxygen-containing organic compound adsorbent
[0086] Copper salt solution soaking treatment: 50 g of 13X molecular sieve and 0.1 g of isopropyl trimethoxysilane were added to 40 g of anhydrous ethanol, stirred at 15°C for 1 h, and then filtered. The filtered molecular sieve was calcined at 400°C for 0.5 h. The calcined 13X molecular sieve was soaked in a 0.1 mol / L aqueous copper chloride solution at room temperature, with the mass ratio of 13X molecular sieve to copper ions being 1:0.01, for 24 h.
[0087] Titanium precursor sol treatment: 10 g of titanium silicate was slowly added dropwise to a mixed solvent of 30 g of ethanol and 5 g of distilled water, stirred at 50°C for 1 h, to obtain a titanium precursor sol.
[0088] The 13X molecular sieve soaked in the copper salt solution was added to the titanium precursor sol, stirred uniformly (time 6 h, temperature 80°C), and the mixture was dried at 90°C for 6 h, and then heated to 450°C at a heating rate of 5°C / min in a kiln, and calcined for 0.5 h. The calcined product was dried in a vacuum drying device for 12 h, and finally an oxygen-containing organic compound adsorbent was obtained.
[0089] Example 3
[0090] (1) Preparation of 13X molecular sieve seeds
[0091] This step is the same as (1) in Example 1.
[0092] (2) Preparation of 13X molecular sieve (introducing waste catalyst)
[0093] 5 g of 200-mesh waste ZSM-5 molecular sieve (composition see Table 1) was mixed uniformly with 6 g of 200-mesh waste 13X adsorbent (composition see Table 1) and 10% by mass Na2CO3, calcined at 650°C for 120 min, and then dissolved with a 15% by mass nitric acid solution to obtain a 1.2 mol / L aluminum-rich solution for standby use. 15 g of the residue obtained by filtration, 8 g of NaOH, and 45 g of H2O were mixed uniformly and filtered to obtain a 2 mol / L silicon-rich solution. Finally, the silicon-rich solution and the aluminum-rich solution were mixed in a weight ratio of 5.5:1 to obtain a gel-like mother liquor. The molar ratio of SiO2 to Al2O3 in the gel-like mother liquor was 0.5:1, the molar ratio of Na2O to SiO2 was 6:1, and the molar ratio of H2O to SiO2 was 10:1.
[0094] 20 g of 13X molecular sieve seeds were added to the gel-like mother liquor and stirred at 60°C for 12 h of aging. The mixture was placed in a hydrothermal reactor and crystallized at a temperature of 105°C for 20 h. The reaction product was filtered and washed to pH 7, and then dried at 90°C to obtain 13X molecular sieve.
[0095] (3) Preparation of oxygen-containing organic compound adsorbent
[0096] Copper salt solution soaking treatment: 50 g of 13X molecular sieve and 2.5 g of tetraethyl orthosilicate were added to 100 g of anhydrous ethanol, and stirred at 40°C for 10 h, and then filtered. The filtered molecular sieve was calcined at 500°C for 4 h. The calcined 13X molecular sieve was soaked in 2 L of a copper acetate aqueous solution at room temperature, and the mass ratio of the 13X molecular sieve to copper ions was 1:0.05, and the soaking was continued for 30 h.
[0097] Titanium precursor sol treatment: 10 g of titanium diisopropoxy bisacetylacetone was slowly added dropwise to a mixed solvent of 70 g of ethanol and 15 g of distilled water, and stirred at 70°C for 6 h to obtain a titanium precursor sol.
[0098] The 13X molecular sieve soaked in the copper salt solution was added to the titanium precursor sol, and stirred uniformly (time 7 h, temperature 70°C), and the mixture was dried at 110°C for 18 h, and then heated to 550°C at a heating rate of 5°C / min in a kiln, and calcined for 4 h. The calcined product was dried in a vacuum drying device for 12 h, and finally an oxygen-containing organic compound adsorbent was obtained.
[0099] Example 4
[0100] (1) Preparation of 13X molecular sieve seeds
[0101] The same as (1) in Example 1.
[0102] (2) Preparation of 13X molecular sieve (introducing waste catalyst)
[0103] 10 g of 200 mesh waste ZSM-5 molecular sieve catalyst (see Table 1 for composition) was mixed uniformly with 8 g of 10% by mass Na2CO3, and calcined at 650°C for 120 min, and then dissolved with a 25% by mass nitric acid solution to obtain 1.2 mol / L of an aluminum-rich liquid for standby use. 10 g of the filtered residue, 6 g of NaOH, and 40 g of H2O were mixed uniformly and filtered to obtain 2 mol / L of a silicon-rich liquid. Finally, the silicon-rich liquid and the aluminum-rich liquid were mixed in a weight ratio of 2.5:1 to obtain a gel-like mother liquor. The molar ratio of SiO2 to Al2O3 in the gel-like mother liquor was 3.5:1, the molar ratio of Na2O to SiO2 was 2.8:1, and the molar ratio of H2O to SiO2 was 80:1.
[0104] 30 g of 13X molecular sieve seeds were added to the gel-like mother liquor, and stirring and aging were continued at 70°C for 152 h. The reaction product was placed in a hydrothermal reaction, the crystallization temperature was 115°C, and the crystallization time was 16 h. The reaction product was filtered and washed to pH 7, and dried at 90°C to obtain 13X molecular sieve.
[0105] (3) Preparation of adsorbent for oxygen-containing organic compounds
[0106] The same as (3) in Example 1.
[0107] Example 5
[0108] (1) Preparation of 13X molecular sieve seeds
[0109] The difference from (1) in Example 1 is that the temperature of the first-stage crystallization is 20°C, the temperature of the second-stage crystallization is 40°C, and the other steps are the same as (1) in Example 1.
[0110] (2) Preparation of 13X molecular sieve (introducing waste catalyst)
[0111] The same as (2) in Example 1.
[0112] (3) Preparation of adsorbent for oxygen-containing organic compounds
[0113] The same as (3) in Example 1.
[0114] Example 6
[0115] (1) Preparation of 13X molecular sieve seeds
[0116] The difference from (1) in Example 1 is that the temperature of the first-stage crystallization is 60°C, the temperature of the second-stage crystallization is 80°C, and the other steps are the same as (1) in Example 1.
[0117] (2) Preparation of 13X molecular sieve (introducing waste catalyst)
[0118] The same as (2) in Example 1.
[0119] (3) Preparation of adsorbent for oxygen-containing organic compounds
[0120] The same as (3) in Example 1.
[0121] Example 7
[0122] (1) Preparation of 13X molecular sieve seeds
[0123] The same as (1) in Example 1.
[0124] (2) Preparation of 13X molecular sieve (introducing waste catalyst)
[0125] The difference from (2) in Example 1 is that the crystallization temperature is 60°C, and the crystallization time is 36 h. The other steps are the same as (2) in Example 1.
[0126] (3) Preparation of adsorbent for oxygen-containing organic compounds
[0127] The same as (3) in Example 1.
[0128] Example 8
[0129] (1) Preparation of 13X molecular sieve seeds
[0130] The same as (1) in Example 1.
[0131] (2) Preparation of 13X molecular sieve (introducing waste catalyst)
[0132] The difference from (2) in Example 1 is that the crystallization temperature is 115°C and the crystallization time is 0.1 h. The remaining steps are the same as (2) in Example 1.
[0133] (3) Preparation of oxygen-containing organic compound adsorbent
[0134] The same as (3) in Example 1.
[0135] Example 9
[0136] (1) Preparation of 13X molecular sieve seeds
[0137] The same as (1) in Example 1.
[0138] (2) Preparation of 13X molecular sieve (introducing waste catalyst)
[0139] The difference from (2) in Example 1 is that the crystallization temperature is 150°C. The remaining steps are the same as (2) in Example 1.
[0140] (3) Preparation of oxygen-containing organic compound adsorbent
[0141] The same as (3) in Example 1.
[0142] Comparative Example 1
[0143] (1) Preparation of 13X molecular sieve seeds
[0144] The difference from (1) in Example 1 is that two-stage crystallization treatment is not used, and one-stage crystallization treatment is used to obtain a seed solution, wherein the temperature of the one-stage crystallization treatment is 40°C and the time is 12 h. The remaining steps are the same as (1) in Example 1.
[0145] (2) Preparation of 13X molecular sieve (introducing waste catalyst)
[0146] The difference from (1) in Example 1 is that the crystallization temperature is 100°C. The remaining steps are the same as (2) in Example 1.
[0147] (3) Preparation of oxygen-containing organic compound adsorbent
[0148] The same as (3) in Example 1.
[0149] Comparative Example 2
[0150] (1) Preparation of 13X molecular sieve seeds
[0151] This step is omitted.
[0152] (2) Preparation of 13X molecular sieve (introducing waste catalyst)
[0153] The difference from (2) in Example 1 is that the weight ratio of the silicon-rich liquid to the aluminum-rich liquid is 9.5:1 to obtain a gel-like mother liquor; the obtained gel-like mother liquor is aged at 70℃ for 15h, and is placed in a hydrothermal reactor for crystallization treatment, wherein the crystallization temperature is 105℃, and the crystallization time is 20h; after filtration and washing, the pH is 7, and the 13X molecular sieve is directly obtained by drying at 90℃.
[0154] (3) Preparation of oxygen-containing organic compound adsorbent
[0155] The same as (3) in Example 1.
[0156] Comparative Example 3
[0157] (1) Preparation of 13X molecular sieve seeds
[0158] 100.0g of water glass (mass fraction of 28%) is dissolved in 18.0g of deionized water to obtain a dispersion phase aqueous solution of a silicon source; 12.5g of pseudoboehmite is dissolved in 25.0g of deionized water, and after pretreatment at 25℃ and 500rpm for 1h in a closed reactor, an aqueous solution of an aluminum source is obtained; the aqueous solution of the aluminum source is slowly added to the aqueous solution of the silicon source, and stirring is continued at 45℃ for 24h to obtain a mixed system; 20.2g of NaOH is dissolved in 15g of deionized water to obtain a NaOH solution. The NaOH solution is added to the mixed system, and the pH value is controlled to be maintained at 13 to obtain a system to be crystallized; the system to be crystallized is transferred to a hydrothermal reactor for temperature-controlled crystallization, and the temperature of the crystallization treatment is 100℃, and the time is 18h; the reaction product is filtered and washed to a pH of 7, and is dried at 90℃ to obtain 13X molecular sieve.
[0159] (2) Preparation of 13X molecular sieve (introducing waste catalyst)
[0160] This step is omitted.
[0161] (3) Preparation of oxygen-containing organic compound adsorbent
[0162] The same as (3) in Example 1.
[0163] Comparative Example 4
[0164] (1) Preparation of 13X molecular sieve seeds
[0165] The difference from (1) in Example 1 is that the temperature of the first crystallization treatment is 70°C and the temperature of the second crystallization treatment is 75°C. The remaining steps are the same as in (1) in Example 1.
[0166] (2) Preparation of 13X molecular sieves (introduction of waste catalyst)
[0167] The same as (2) in Example 1.
[0168] (3) Preparation of oxygen-containing organic compound adsorbent
[0169] The same as (3) in Example 1.
[0170] Comparative Example 5
[0171] (1) Preparation of 13X molecular sieve seeds
[0172] The same as (1) in Example 1.
[0173] (2) Preparation of 13X molecular sieves (introduction of waste catalyst)
[0174] The same as (2) in Example 1.
[0175] (3) Preparation of oxygen-containing organic compound adsorbent
[0176] This step is omitted.
[0177] Comparative Example 6
[0178] (1) Preparation of 13X molecular sieve seeds
[0179] The same as (1) in Example 1.
[0180] (2) Preparation of 13X molecular sieves (introduction of waste catalyst)
[0181] The same as (2) in Example 1.
[0182] (3) Preparation of oxygen-containing organic compound adsorbent
[0183] The difference from (3) in Example 1 is that the copper salt solution immersion treatment is not performed. The remaining steps are the same as in (3) in Example 1. The specific steps include:
[0184] Example 1 (1) Preparation of 13X molecular sieve seed
[0185] Comparative Example 7
[0186] (1) Preparation of 13X molecular sieve seed
[0187] The same as (1) in Example 1.
[0188] (2) Preparation of 13X molecular sieve (introducing waste catalyst)
[0189] The same as (2) in Example 1.
[0190] (3) Preparation of oxygen-containing organic compound adsorbent
[0191] The difference from (3) in Example 1 is that the titanium precursor sol treatment is not performed. The remaining steps are the same as (3) in Example 1. The specific steps include:
[0192] The 50 g of 13X molecular sieve and 0.5 g of methyl triethoxysilane were added to 49.5 g of anhydrous ethanol, stirred at room temperature for 4 h, then filtered, and the filtered molecular sieve was calcined at 450°C for 2 h; the calcined 13X molecular sieve was soaked in a 1 mol / L aqueous copper nitrate solution at room temperature for 24 h; the 13X molecular sieve after soaking in the copper salt solution was dried at 100°C for 12 h, and then heated to 500°C at a heating rate of 5°C / min in a kiln, and calcined for 2 h. The calcined product was dried for 12 h in a vacuum drying device, and finally an oxygen-containing organic compound adsorbent was obtained.
[0193] Test method:
[0194] Silicon-aluminum ratio of 13X molecular sieve: X-ray fluorescence spectroscopy (XRF), the results are shown in Table 3;
[0195] Pore volume and specific surface area of 13X molecular sieve: BET test method, the results are shown in Table 3;
[0196] Adsorption performance of the organic oxygenate adsorbent: The total product of Fischer-Tropsch synthesis was used as the adsorption object, which was passed through the fixed bed containing the adsorbent, and the concentration change of the product before and after passing through the bed and the concentration change of the oxygen-containing compound impurities were monitored, and the removal rate of the oxygen-containing organic compound impurities and the loss rate of the target product were calculated, and the calculation results are shown in Table 3. Among them, the adsorption temperature was 55°C, the pressure was 1 atm, the weight ratio of the adsorbent and the Fischer-Tropsch synthesis product was 1:10, the adsorbent loading was 1 g, the sample was introduced into the fixed bed reactor at a flow rate of 10 ml / min, the adsorption time was 2 hours, and the content of each component in the Fischer-Tropsch synthesis product before treatment (in terms of weight percentage) is shown in Table 2.
[0197] BJH adsorption average pore size: The adsorption / desorption isotherm of the sample at liquid nitrogen temperature was determined by a nitrogen adsorption instrument, and the pore size distribution was calculated using the BJH model to obtain the adsorption average pore size.
[0198] Silicon source conversion rate: The silicon content in the reaction product and the initial silicon source was determined by chemical dissolution method and ICP-OES analysis, and the conversion rate was calculated.
[0199] The composition of the waste catalyst used in the above examples and comparative examples is shown in Table 1.
[0200] Table 1:
[0201] Spent catalyst name Fe203 / wt% Al2O3 / wt% SiO2 / wt% SO3 / wt% CaO / wt% Spent ZSM-5 molecular sieve catalyst 0.050 19.84 79.64 0.31 0.18 Spent 13X adsorbent 0.020 72.36 18.0 0.024 0.042 .
[0202] Table 2 lists the content of each component in the Fischer-Tropsch synthesis product before treatment (in terms of weight percentage).
[0203] Table 2:
[0204]
[0205] Table 3 lists the silicon-aluminum ratio, BET specific surface area, pore volume, BJH adsorption average pore size, silicon source conversion rate and adsorption performance of the oxygen-containing organic compound adsorbent of the molecular sieves prepared in the above examples and comparative examples of the application. It should be noted that in Table 3, micropores refer to pores with a pore size of <2 nm, and mesopores refer to pores with a pore size of 2-50 nm.
[0206] Table 3:
[0207]
[0208]
[0209] From the above description, it can be seen that the above-mentioned embodiments of the present application achieve the following technical effects: by utilizing the advantages of 13X molecular adsorption sites and large internal pore volume of molecular sieve crystals, and by introducing a coupling agent and metal ions for impregnation treatment, the surface and structure of the 13X molecular sieve are modified, thereby obtaining an adsorbent with improved performance. The adsorbent has excellent chemical stability, thermal stability, and high adsorption efficiency for oxides, and not only performs excellently in the removal of oxides in Fischer-Tropsch synthesis high-carbon alkane-alkene products, but is also suitable for efficient removal of oxides in a wide range of hydrocarbon fuels or chemical products, thereby providing a high-efficiency, stable, and controllable solution for the related field.
[0210] The above merely describes preferred embodiments of the present application and is not intended to limit the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for producing an adsorbent of an oxygen-containing organic compound, characterized by, The preparation method comprises: 13X molecular sieves and coupling agent are added into an alcohol solvent, and solid-liquid separation and first calcination are sequentially performed to obtain an adsorbent precursor; The adsorbent precursor is soaked in a copper salt solution, and then mixed with a precursor sol formed by mixing a titanium source, ethanol and water, and sequentially subjected to first drying, second calcination and second drying to obtain the oxygen-containing organic compound adsorbent. The preparation method of the 13X molecular sieves comprises: Step S1, an aluminum source and a silicon source are mixed with water respectively to obtain aluminum-containing material and silicon-containing material; Step S2, the aluminum-containing material and the silicon-containing material are mixed, and sequentially subjected to first stirring, pH value adjustment and two-stage crystallization treatment to obtain a crystallization product; Step S3, the molecular sieve-containing material is subjected to aluminum dissolution and silicon dissolution treatment to obtain an aluminum-rich liquid and a silicon-rich liquid, and the obtained aluminum-rich liquid and silicon-rich liquid are mixed to obtain a gel-like mother liquor; Step S4, the crystallization product and the gel-like mother liquor are mixed, and sequentially subjected to aging, hydrothermal crystallization, filtration, washing and drying to obtain the 13X molecular sieves; In the two-stage crystallization treatment, the temperature of the first-stage crystallization is 20-60℃, and the time is 4-24h; the temperature of the second-stage crystallization is 80-120℃, and the time is 6-48h; and the two-stage crystallization treatment is performed in a hydrothermal reaction kettle; The molecular sieve-containing material is selected from any one or more of waste ZSM-5 molecular sieve catalyst, waste MTO catalyst, waste molecular sieve adsorbent, waste FCC catalyst or waste VOCs adsorbent; The coupling agent comprises isopropyl trimethyl silane, vinyl trimethyl silane or tetraethyl orthosilicate.
2. The production method according to claim 1, characterized by, The alcohol solvent comprises ethanol, propanol or butanol.
3. The preparation method according to claim 2, characterized in that, The copper salt in the copper salt solution comprises copper nitrate, copper chloride or copper acetate.
4. The preparation method according to claim 2, characterized in that, The titanium source comprises tetrabutyl titanate, titanium silicate or titanium diisopropoxy bisacetylacetone.
5. The preparation method according to claim 2, characterized in that, The mass ratio of the 13X molecular sieves, the coupling agent and the alcohol solvent is 1:(0.01-0.05):(0.8-1.5).
6. The preparation method according to claim 2, characterized in that, The temperature of the first calcination is 400-500℃, and the time is 0.5-4h.
7. The preparation method according to claim 2, characterized in that, The mass ratio of the adsorbent precursor to copper ions in the copper salt solution is 1:(0.01-0.05).
8. The preparation method according to claim 7, characterized in that, The adsorbent precursor is soaked in the copper salt solution for 18-30h.
9. The preparation method according to claim 7, characterized in that, The adsorbent precursor is mixed with the precursor sol for 6-8h at a temperature of 60-80℃.
10. The method of claim 2, wherein, The precursor sol is prepared by second stirring of the titanium source, the ethanol and the water, the time of the second stirring is 1-6h, and the temperature is 50-70℃.
11. The method of claim 2, wherein, The mass ratio of the titanium source, the ethanol and the water in the precursor sol is 1:(3-7):(0.5-1.5).
12. The method of claim 2, wherein, The temperature of the first drying is 90-110℃, and the time is 6-18h.
13. The method of claim 2, wherein, The temperature of the second calcination is 450-550℃, and the time is 0.5-4h.
14. The method of claim 2, wherein, The temperature of the second drying is 70-90℃, and the time is 8-16h.
15. The method of claim 1, wherein, The aluminum source is selected from any one or more of sodium aluminate, pseudo-boehmite, aluminum sulfate or aluminum nitrate.
16. The method of claim 1, wherein, The silicon source is selected from any one or more of the following: silica sol, tetraethyl orthosilicate, coarse-pored silica gel, silicon powder, fly ash or white carbon black.
17. The method of claim 1, wherein, The first stirring condition in step S2 is stirring at 20-100°C for 0.1-24h.
18. The method of claim 1, wherein, The molar ratio of the components in the crystallization product is SiO2 / Al2O3=0.01-2.5:1, Na2O / SiO2=0.01-4.0:1, and H2O / SiO2=1.0-40.0:
1.
19. The method of claim 1, wherein, The steps of dissolving aluminum and dissolving silicon are as follows: 1) The ground molecular sieve-containing material less than 200 mesh is mixed with Na2CO3 at a mass ratio of 1:0.5-1:5, and a calcination product is obtained after calcination at 550-800°C for 60-120min. The calcination product is dissolved in a monobasic acid with a mass fraction of 10%-35%, and a filtrate and a residue are obtained after filtration. The filtrate is the aluminum-rich solution; 2) The residue is mixed with NaOH and H2O at a mass ratio of (2-100):(40-60):(50-400), and a silicon-rich solution is obtained after third stirring, mixing, and filtration.
20. The method of claim 1, wherein, The molar ratio of the components in the gel-like mother liquor is SiO2 / Al2O3=(0.5-6.0):1, Na2O / SiO2=(0.5-6.0):1, and H2O / SiO2=(10-100):
1.
21. The method of claim 1, wherein, The amount of the crystallization product added is 5wt%-20wt% of the gel-like mother liquor.
22. The method of claim 1, wherein, The aging temperature is 20-100°C, and the aging time is 0.1-24h. The aging process is carried out under the fourth stirring condition.
23. The method of claim 1, wherein, The temperature of the hydrothermal crystallization in step S4 is 60-150°C, and the time is 0.1-36h.
Citation Information
Patent Citations
A method for synthesizing submicron X-type molecular sieves and its application
CN103523796B
13X zeolite molecular sieve, preparation method therefor and application of 13X zeolite molecular sieve
CN106542542A
Molecular sieve as well as preparation method and application thereof
CN117899810A